Profil Sel Darah Merah Monyet Ekor Panjang (Macaca fascicularis) Obes yang Hidup Liar di Pura Uluwatu, Bali - Darmawan, Agus Wawan; Soma, I Gede; Wandia, I Nengah (Veterinary Science and Medicine Journal, 2015)
The aim of this study was to determine the profile of red blood cells in obese long-tailed macaques. A totalof 16 long-tailed macaques was arrested, and then blood samples were collected aseptically and stored inEDTA vacutainer. Twelve out of 16 were classified obese which is determined by body mass index (BMI).The results showed that the average number of erythrocytes 6.08±0.87 (x1061,2*/mm), the levels ofhemoglobin 11.98±1.59 (g/dl), hematocrit value 37.5±3.55 (%), MCV 62.12±5.35 (fl), MCH 19.91±2.06(pg), and MCHC 32.15±4.22 (g/dl) in average. It can be concluded that the red blood cell profile of theobese long-tailed macaques is still in normal range.
Keywords: long-tailed macaques; profile of red blood cells; obese